Brief Notes: Logarithmic Screw Dislocation - Wesołowski, Z. (Engineering Transactions, 2004)
Basing on linear elasticity, the displacement field $u_z =Bϑ \ln r$ (in cylindrical coordinates $r, ϑ, z$) was derived. This displacement has a jump on the half-plane $ϑ = 0$. Stresses orthogonal to this discontinuity plane are continuous.